On the Numerical Simulation of Packed Bed Membrane Reactors for Methanol Synthesis from CO2 and H2: Suitable Alternatives to Packed Bed Reactor Technology - Mejía Galarza, William Andrés; Herguido Huerta, Javier; Menéndez Sastre, Miguel Alejandro (Jornada de Jóvenes Investigadores del I3A, 2019)
Methanol is considered to be a potential energy carrier. Currently, its synthesis from CO2 is performed in conventional reactors, although its yield can be improved if a packed bed membrane reactor (PBMR) is used instead. The objective of this work is to select potential PBMRs as an alternative to the conventional ones.